Offline vs. Online Retail in the Sports Equipment Sector. - Martín-García, María del Mar; Ruiz-Real, José Luis; Gázquez-Abad, Juan Carlos; Uribe-Toril, Juan (Springer, 2025)
In recent years, the growth of online commerce, mainly driven by digitalization, is causing a paradigm shift in retailing. In this scenario, online commerce has become a shopping option that can almost replace the physical shop. However, some consumers still prefer the experience of being able to interact with the product, especially in some sectors, such as the sporting goods trade. Through a sample of 153 participants, this research aims to obtain an approximation of the factors that influence customer satisfaction in the online and offline shop in the sports context. The results show that product variety remains the most influential factor in the satisfactory shopping experience in both environments. Although 46.4% of respondents prefer offline shopping, almost 34% are indifferent to it, which may be an opportunity for retail to evolve, integrating both environments, adding value to the service provided to the customer.
Keywords: Deportes; Marketing; Consumidores - Conducta; Sports retail; Online commerce; Offline commerce; Consumer trends; Product variety